Early life environment affects behavior, welfare, gut microbiome composition, and diversity in broiler chickens - de Jong, Ingrid C.; Schokker, Dirkjan; Gunnink, Henk; van Wijhe, Maudia; Rebel, Johanna M. J. (Frontiers in Veterinary Science, 2022)
This study aimed to identify whether early-life conditions in broiler chickens could affect their behavior and welfare, and whether or not this was associated with an altered gut microbiome composition or diversity. Broilers were tested in a 2 x 2 factorial design with hatching conditions [home pen (OH) or at the hatchery (HH)] and enrichment (dark brooder (EE) or no brooder (NE) until 14 days of age) as factors (N = 6 per treatment combination). Microbiota composition was measured in the jejunum on days (d) 7, 14, and 35 and in pooled fecal samples on day 14. A novel environment test (NET) was performed on days 1 and 11, and the behavior was observed on days 6, 13, and 33. On day 35, composite asymmetry was determined and footpad dermatitis and hock burn were scored. In their home pen, HH showed more locomotion than OH (P = 0.05), and NE were sitting more and showed more comfort behavior than EE at all ages (P <0.001 and P = 0.001, respectively). On days 6 and 13 NE showed more eating and litter pecking while sitting, but on day 33 the opposite was found (age*enrichment: P = 0.05 and P <0.01, respectively). On days 1 and 11, HH showed more social reinstatement in the NET than OH, and EE showed more social reinstatement than NE (P <0.05). Composite asymmetry scores were lower for EE than NE (P <0.05). EE also had less footpad dermatitis and hock burn than NE (P <0.001). Within OH, NE had a more diverse fecal and jejunal microbiome compared to EE on day 14 (feces: observed richness: P = 0.052; jejunum: observed richness and Shannon: P <0.05); the principal component analysis (PCA) showed differences between NE and EE within both HH and OH in fecal samples on day 14, as well as significant differences in bacterial genera such as Lactobacillus and Lachnospiraceae (P <0.05). On day 35, PCA in jejunal samples only showed a trend (P = 0.068) for differences between NE vs. EE within the OH. In conclusion, these results suggest that especially the dark brooder affected the behavior and had a positive effect on welfare as well as affected the composition and diversity of the microbiome. Whether or not the behavior was modulated by the microbiome or vice versa remains to be investigated.